THE INTERVENTION OF THE HUMAN MILK BANK (HMB) IN COMBATING EARLY WEANING: SANITARY RIGOR AND NUTRITIONAL PRIORITIES UNDER RDC NO. 918/2024 (Editora Impacto Científico, 2025)
This study investigated the relevance of breastfeeding and the role of the Brazilian Human Milk Bank Network (rBLH-BR), using a literature review in the Scielo database and analysis of current legislation, focusing on the Collegiate Board Resolution (RDC) No. 918/2024 from ANVISA (Brazilian Health Regulatory Agency). Human milk is undeniably the most complete food, providing immunological, nutritional, and psychological benefits for both the infant, by reducing child mortality and chronic diseases, and the mother, by decreasing risks of hemorrhage and cancer. Human Milk Banks emerge as an essential public health strategy, being a vital link in the chain of food production and distribution in healthcare. These services, supported by government campaigns to encourage donation, follow strict hygienic-sanitary protocols from collection to pasteurization, ensuring the quality of Pasteurized Holder Human Milk (PHHM). PHHM distribution clinically prioritizes hospitalized premature and low-birth-weight newborns, reinforcing the importance of HMBs as a nutritional safeguard and a strategic element for child development.DOI: https://doi.org/10.56238/edimpacto2025.090-030